The Role of Knowledge Management in Achieving Quality Scientific Research An Empirical Study of the Opinions of a Sample of Faculty Members at the College of Commerce and the College of Administration and Economics at the University of Sulaimani - Suza Mohammed Qadir; Falah Hassan Ahmed; Shilan Fazil Mahmoud (The Scientific Journal of Cihan University– Sulaimaniya, 2020)
The research dealt with the concept of knowledge management and its role in improving the quality of scientific research. This study aimed to highlight the role of knowledge management in its dimensions (generation of knowledge, knowledge storage, knowledge distribution, application of knowledge) in order to ensure the achievement of the quality of scientific research, by addressing the main problem about the possibility The application of knowledge management to achieve quality in scientific research in academic institutions, the descriptive approach was adopted in the theoretical side. As for the applied side, a questionnaire was adopted to collect the primary information and then distribute it to the research sample. In light of this, data was collected and analyzed and hypotheses tested The statistical program (SPSS) was used for this purpose, and the research reached a number of results, the most important of which are, there is a statistically significant relationship to knowledge management with its dimensions (knowledge generation, knowledge storage, knowledge distribution, application of knowledge) on the quality of scientific research, and one of the most important recommendations presented by the research is the need to establish and develop the concept of knowledge management among the faculty members to ensure quality in scientific research and achieve the goals of the university and the need to increase excellence awards for researchers and give it more attention.